Revolutionizing Construction Safety: Unveiling the Digital Potential of Building Information Modeling (BIM) - Bilal Manzoor; Rabia Charef; Maxwell Fordjour Antwi-Afari; Khalid Saqer Alotaibi; Ehsan Harirchian (Buildings)
The construction industry is facing issues worldwide, particularly worker fatalities and injury rates. Construction safety requires careful attention and preparation across the project’s entire lifecycle, from design to demolition activities. In the digital era, Building Information Modeling (BIM) has emerged as a transformative technology in the construction industry, offering new opportunities to enhance safety standards and reduce accidents. This study examines the influence of BIM on construction safety, particularly its capacity to transform safety protocols, enhance danger identification, and minimize accidents during the construction project’s duration. The review approach used is based on PRISMA. Scopus and Web of Science were the databases used to search for qualifying publications. From an initial cohort of 502 papers, 125 were chosen as relevant to the scope of this research. A thorough analysis of the existing literature was conducted to examine the processes by which BIM helps to improve safety, such as early hazards identification, conflict detection, virtual safety simulations, and improved communication and collaboration among project stakeholders. This study examined the following knowledge gaps: integration with safety regulations and standards, a comprehensive safety dimension in BIM, BIM for real-time safety monitoring, and a BIM-driven safety culture. The following potential future research directions were highlighted: enhanced BIM applications for safety, longitudinal studies on BIM and safety outcomes, BIM for post-construction safety and maintenance, and BIM for safety training and simulation. In conclusion, the integration of BIM into construction safety protocols presents significant potential for mitigating risks and improving safety management over the asset lifecycle. As the industry increasingly adopts digital technology, BIM will be crucial in establishing safer and more efficient construction environments.